Monoclonal IgM Antibodies Targeting Candida albicans Hyr1 Provide Cross-Kingdom Protection Against Gram-Negative Bacteria - Youssef, Eman G.; Zhang, Lina; Alkhazraji, Sondus; Gebremariam, Teclegiorgis; Singh, Shakti; Yount, Nannette Y.; Yeaman, Michael R.; Uppuluri, Priya; Ibrahim, Ashraf S. (Frontiers in Immunology, 2020)
Recent years have seen an unprecedented rise in the incidence of multidrug resistant (MDR) Gram-negative bacteria (GNB) such as Acinetobacter and Klebsiella species. In view of the shortage of novel drugs in the pipeline, alternative strategies to prevent and treat infections by GNB are urgently needed. Previously, we have reported that the C. albicans hyphal-regulated protein Hyr1 shares striking 3-dimensional structural homology with cell surface proteins of A. baumannii. Moreover, active vaccination with rHyr1p-N or passive immunization with anti-Hyr1p polyclonal antibody, protect mice from Acinetobacter infection. In the present study, we use molecular modeling to guide design of monoclonal antibodies (mAbs) generated against Hyr1p and show them to bind to priority surface antigens of Acinetobacter and K. pneumoniae. The anti-Hyr1 mAbs block damage to primary endothelial cells induced by the bacteria, and protect mice from lethal pulmonary infections mediated by A. baumannii or K. pneumoniae. Our current studies emphasize the potential of harnessing Hyr1p mAbs as a cross-kingdom immunotherapeutic strategy against MDR GNB.